Quality of Life, Pain and Depression in Patients with Hemodialysis - Berna Tander; Dilek Durmuş; Yeşim Akyol; Ferhan Cantürk (Archives of Rheumatology, 2008)
Objective: We aimed to evaluate the quality of life, severity of pain and psychological states of patients with end stage chronic renal disease undergoing hemodialysis and to make a correlation analysis between subitems of Short Form-36 (SF-36) and severity of pain and depression. Materials and Methods: Fifty-two patients with hemodialysis and 54 controls were enrolled in the study. The social and demographic characterictics of the patients were evaluated by semi structured form. All of the patients and control cases underwent Visual Analog Scala (VAS), Beck Depression Inventory (BDI) and SF-36. Results: There was no statistical difference between the patients and control cases according to demographical data (p>0.05). The SF-36 scores of the study patients were significantly lower than controls except in the Physical Role (PR) score (p<0.05). The subparameters of the SF-36 measurements were negative correlated to the BDI score except PR (r=-0.06, p>0.05) score (p<0.01). The pain by VAS score was found to negative correlate with the SF- 36 subitems of PR (r=-0.37, p<0.01), Pain (r=-0.35, p<0.05) and Social Function (r=-0.35, p<0.01). Furthermore, it was found that a negative correlation between duration of dialysis and Physical Function score (r=-0.42, p<0.01) and positive correlation between duration of dialysis and vitality score (r= 0.35, p<0.05). Conclusion: The follow-up criteria of the patients with hemodialysis should be questioned by quality of life and emotional states. Depression should be evaluated and if present it should be treated properly. (Rheumatism 2008; 23: 72-6)